Exploring horses’ (Equus caballus) gaze and asymmetric ear position in relation to human attentional cues - Gabriela Barrera; Anna Albiach-Serrano; Federico Guillén-Salazar (Animal Cognition)
Abstract Studies have shown that horses are sensitive to human attentional cues. Also, there is some evidence that they might be able to infer the knowledge state of a human and communicate intentionally with us. However, this ability is not fully characterized and certain behaviors, like gaze, asymmetric ears position or vocalizations, which could work as attention-getting behaviors, have been scarcely studied in this context. The aim of the present study was to assess whether horses’ gaze toward a person, asymmetric ears position and vocalizations are subject to audience effects and adjust to human attentional cues, which would suggest a communicative function. For this purpose, we adapted a protocol used with domestic dogs [Kaminski et al. 2017] and observed horses’ spontaneous behavior (gaze, asymmetric ears position and vocalizations) in the presence of a human holding and not holding food in an attentive position (facing the horse with open eyes) and in a non-attentive position (with her back turned towards the horse). We found significant evidence of horses being sensitive to human attentional cues (reflected in the horses’ gaze duration and asymmetric position of the ears), but not of intentional communication towards humans.